Paraklet a grzech świata (J 16, 7-11) - Kudasiewicz, Józef (The Biblical Annals, 2017)
The paper consists of three parts: 1. Text and context. There has been presented the relation of the pericopes with one another as well as with their context. Those pericopes are devoted to Paraclete. They belong to the farewell speech of Jesus (J 13, 1-16, 33). The disciples are upset about the Master’s imminent departure; He promisses them that we will not leave them alone. 2. The departure of Jesus and the coming of Paraclete. The sending of the Holy Spirit is a specific act made by God. That is why Jesus will send His Spirit only then when He will reveal fully His godhead through adoration. Paraclete may start His entire activity after the revelation has been completed. Paraclete is at the service of this revelation. 3. The sin of the world. Paraclete will reveal the sin of the world; He will do it in the hearts and consciences of the disciples; He will convince them that the world is guilty. The world means here this part of humanity who is under Satan and persists in error and sin. The world is not only unable to receive Paraclete but is also hostile towards Him.